FUTURES GOLD WAQF ACCOUNTING: CHALLENGES AND OPPORTUNITIES IN SHARIA FINANCIAL REPORTING - Santi Deswita; Himmatul Khairi; Septria Susanti; Muhammad Rais (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
Term gold waqf is an innovative waqf practice that has developed in society with the aim of increasing the productive potential of waqf assets. However, the application of accounting for term gold waqf still faces challenges in sharia financial reporting. This article aims to describe and analyze the challenges and opportunities in sharia financial reporting for term gold waqf. The method used is a descriptive qualitative study. The research findings indicate that the main challenge in Islamic financial reporting is the absence of specific reporting standards governing the recognition, measurement, presentation, and reporting of gold endowment futures. Additionally, the lack of human resource competence in Islamic accounting, as well as gold price fluctuations, pose challenges for endowment management institutions. On the other hand, there are also opportunities to improve Islamic financial literacy, namely through regulatory support or the development of PSAK 112 in line with contemporary waqf practices. The potential for partnerships between waqf management institutions and Islamic financial institutions, as well as Islamic financial reporting based on Fintech, provides opportunities for accounting for gold waqf. This research is expected to serve as a foundation for the development of accounting standards, particularly PSAK 112, and as a technical guideline for the recognition, measurement, presentation, and disclosure of accountable and sharia-compliant gold wakaf futures